The Effect of Work-Life Balance, Motivation, and Communication on Employee Job Satisfaction at PT Transkon Jaya Tbk - Hadiyatno, Didik; Yuliani, Tutik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Human resource talent development is very important for a company because good human resource development can create a capability that will be a strength in running the company's business and as a tool to achieve the company's vision and mission to be better in the future. To create employees who have good abilities, companies must have a formula for developing these capabilities. One of the stimuli that can encourage this is job satisfaction. Therefore, the purpose of this study is to determine the effect of work-life balance, motivation, and communication on employee job satisfaction at PT Transkon Jaya Tbk. This study was conducted at PT Transkon Jaya Tbk, with a population of 150 using the census method with 150 respondents, this research method uses a quantitative research method. Data collection by observation and distribution of questionnaires. The data analysis tool used is Smart PLS4. The results of the study showed that the variables work-life balance, motivation, and communication have a significant effect on employee job satisfaction at PT Transkon Jaya Tbk.